39 Care Home Liaison Role- Bridging the Gap Between Acute Hospitals and Care Homes. (6th February 2020) - Sendall, C; Wright, P; Downes, R
Abstract: Introduction: There are over 400, 000 people over 65 in UK care homes, three times the number than that in acute hospitals. They are amongst the frailest in our community, with average life expectancy of 15months once in the home. Their needs are often complex and challenging, which when unmet, often result in unwanted and unnecessary hospital admissions. Imperial College Healthcare Trust (ICHT), along with funding from Health Education England (HEE), have introduced a care home liaison nurse. The aim is to bridge the boundaries, making a significant difference to cross organisation communication and support. Methods: The care home liaison nurse manages a frailty liaison service with the largest local nursing care home. This home has 140 residents with complex needs. The care home liaison nurse provides a point of contact for advice, guidance and support for individual patient pathways, she provides face to face assessment and treatment or verbal advice. In addition, the nurse supports discharge from the acute setting. This direct contact allows rapid access to specialist advice, and aims to build confidence both within the care home team and within the acute team, that the patients' needs can be met in their own surroundings. Results: The preliminary data demonstrates a positive impact this role is having both to the acute trust and most importantly patient's experience. Comparing ICHT data from April-May 2018 to April-May 2019 it showing that the number of avoidable admissions has decreased from 54.3% to 37.5%, length of stay when patients are admitted has decreased from 11.7 days to 6.5 days, and the number of patients with an advanced care plan has risen 14.9%. Feedback from nursing staff at the care centre as well as that from patients and families has been overwhelmingly positive. Conclusions: The role is still in the pilot phase. Given the already positive impact it is hoped that it will continue and expand into other care homes and extra sheltered accommodations.